Case report on the importance of longitudinal analysis of left ventricular end-systolic volume, rather than ejection fraction, in a heart transplant patient. Issue 6 (29th May 2021) - Kerkhof, Peter L M; Heyndrickx, Guy R
Abstract: Background: Sequential determinations of left ventricular (LV) volume constitute a cornerstone in the mechanical performance evaluation of any heart transplant (HTX) patient. A comprehensive analysis of volumetric data offers unique insight into adaptation and pathophysiology. Case summary: With a focus on eight sequential biplane angiocardiographic LV end-systolic volume (ESV) determinations, we evaluate the clinical course of a male patient following HTX (female donor) at the age of 61 years. This former smoker had a history of chronic obstructive pulmonary disease, hypertension, and hypercholesterolaemia refractory to treatment, and presented with multivessel coronary artery disease. The later course was complicated by pulmonary hypertension, an abdominal aortic aneurysm, and secondary chronic kidney disease. After an additional episode of pulmonary embolism, the patient died at the age of 79. At one point, the ESV was > 700% higher than the starting value, and actually by far exceeded the relative change of any other volume-based metric evaluated, including ejection fraction (EF). Discussion: The longitudinal study of LV volumetric data in HTX patients offers a unique window to the pathophysiology of remodelling and sex-specific adaptation processes. The present case documents that proper analysis of serial findings form a rich source of clinically relevant information regarding disease progression. End-systolic volume is the primary indicator, in contrast to the popular metric EF. This finding is supported by population-based studies reported in the literature. We conclude that comprehensive analysis of volumetric data, particularly ESV, contributes to personalized medicine and enhances insight into LV (reverse) remodelling, while also informing about prognosis.